Laser-driven ablation through fast electrons in PALS experiment. (March 2016) - Gus'kov, S.Yu.; Chodukowski, T.; Demchenko, N.; Kalinowska, Z.; Kasperczuk, A.; Krousky, E.; Pfeifer, M.; Pisarczyk, P.; Pisarczyk, T.; Renner, O.; Skala, J.; Smid, M.; et al.
Abstract: Energy transfer to shock wave in Al and Cu targets irradiated by a laser pulse with intensity of I≈1-50 PW/cm 2 and duration of 250 ps was investigated at Prague Asterix Laser System (PALS). The iodine laser provided energy in the range of 100-600 J at the first and third harmonic frequencies. The focal spot radius of laser beam on the target was varied from 160 to 40 μm. The dominant contribution of fast electron energy transfer into the ablation process was found when using the first harmonic radiation, the focal spot radius of 40-100 μm, and the energy of 300-600 J. The fast electron heating results in the growth of ablation pressure from 60 Mbar at the intensity of 10 PW/cm 2 to 180 Mbar at the intensity of 50 PW/cm 2 and in the growth of the efficiency of the energy conversion into the shock wave from 2 to 7% under the conditions of 2D ablation.